Developing Virtual Reality (VR) Technology in Learning Arabic Grammar:An Insight on Needs Analysis for Arabic-VR Application - Mohammad Amnan Awang Ali; Mohd. Feham Md Ghalib (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah, Volume 36 Issue 03 Page (15–25)